Chiroptical characterization of homopolymeric block fractions in alginates. (1st August 2016) - Martínez-Gómez, Fabián; Mansilla, Andrés; Matsuhiro, Betty; Matulewicz, María C.; Troncoso-Valenzuela, Marcos A.
Graphical abstract: Highlights: Alkaline extracts were isolated from three brown seaweeds of southern Chile. Partial acid hydrolysis of alginates afforded hetero- and homopolymeric blocks. Homopolymeric blocks were analyzed by CD and ORD chiroptical spectroscopies. Absolute configuration of monomers was determined by CD, ORD, and polarimetry. Abstract: Homopolymannuronic and homopolyguluronic fractions were obtained by partial hydrolysis of the alkaline extracts from the brown seaweeds Ascoseira mirabilis, Desmarestia menziessi, Desmarestia ligulata and Durvillaea sp. collected in southern Chile. Full characterization of the fractions was achieved by FT-IR and NMR spectroscopy. Total hydrolysis with 90% formic acid of the homopolymeric fractions allowed the preparation of mannuronic and guluronic acids. Both monomers and homopolymeric fractions as neutral salts were studied by CD and ORD. Chiroptical spectra were similar in shape and sign to those previously published in the literature, and permitted to assign D configuration to mannuronic acid and L configuration to guluronic acid in alginic acids. Specific optical rotation values at the sodium D light for the homopolymannuronic (∼−100°) and homopolyguluronic (∼−110°) acid fractions were obtained. These high negative values are proposed for the assignment of the absolute configuration of monomers in homopolymeric fractions.